Effect of Heavy Bridles on the Performance of Demersal Trawls - R.S., Manohar Doss; P., George Mathai; Putra, Pravin; K.V., Mohan Rajan (Fishery Technology, 2025)
Heavy manila ropes of 38 mm dia were used as lower bridles in a 25 m high opening trawl and a 32m large mesh demersal trawl to evaluate its efficiency in improving trawl catch, compared to HOPE bridles of 18 mm dia. The difference in catch rates of total catch and constituent groups during comparative fishing operations were not statistically sig- nificant except for Lactarius spin 25m high opening trawl. Heavy bridles therefore appear to have only marginal advantage over light bridles.